Utilization of BSA optimized cascade controller in a renewable energy-based AGC systems - Rambabu Kasukurthi; R. Srinu Naik (International Journal of Applied Power Engineering (IJAPE), 2026)
A novel cascade controller named proportional integral derivative-tilt integral derivative (PID-TID) is proposed for a two-area thermal-wind automatic generation control (AGC) system and its gains are optimized by a novel metaheuristic bird swarm algorithm (BSA). The BSA tuned PID-TID controller enhances dynamics over PID and TID controller in terms of settling time and peak shoots. Moreover, dynamics with wind integration have shown significant improvement over thermal system alone. Further system has shown enhanced dynamics with redox flow batteries (RFB) over thermal-wind system. Furthermore, studies with automatic voltage regulation (AVR) strengthen voltage stability. Also, responses with PID-TID have shown steady dynamic profile at various loading conditions. Integrating wind energy into thermal system results in significant enhancements in dynamics showcasing greater stability. Also, improvements are evident with the RFB introduction, enhance dynamic with in hybrid system. The incorporation of AVR enhance voltage stability. The proposed PID-TID demonstrates significant robustness ensuring stable response under loading condition and effectively boost dynamic performance.